PEMBELAJARAN TRIGONOMETRI DENGAN PENDEKATAN METAKOGNITIF DI KELAS X SMA NEGERI 11 BANDA ACEH - Irma Aryani (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
The background of this study is the students’ difficulties in resolving the problems in trigonometry material. Trigonometry material requires creativity of students so that students are required to build knowledge and learning strategies. Metacognitive approach is one approach that focuses on how the teaching in learning mathematics or the students who are invited to learn and learn to think. The subjects were the students of class X-6 SMA Negeri 11 Banda Aceh. the total sample is 30 students. The approach used in this study is a qualitative approach. The type of this research is one shot case study design (pre-experimental method). The used instrument for data collection is a test of student learning outcomes, teachers' observation sheet for the ability in managing learning and student activities, and student questionnaire responses. The obtained data were processed using percentages, the ideal time criteria, and the description of the average score in order to get information about students’ activities, students’ responses, the ability of teachers in managing the learning and mastery learning. The effectiveness of this learning can be based on (1) Mastery learning, (2) the ability of teachers in managing learning, (3) Activities of students, (4) The response of students. Learning trigonometry with metacognitive approach would be considered effective if at least three of the four aspects are met with the requisite thoroughness aspects of learning outcomes are met (effective). The results showed that metacognitive approach is effective in trigonometry material in class X-6 SMA Negeri 11 Banda Aceh. It is because, (1) the results of student learning is complete, (2) students’ activities are active, and (3) students' response toward learning are positive, and (4) the ability of teachers in managing learning are in good or excellent criteria.